2012
DOI: 10.1364/boe.3.000388
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular optical coherence tomography intensity kurtosis: visualization of vasa vasorum in porcine carotid artery

Abstract: Application of speckle variance optical coherence tomography (OCT) to endovascular imaging faces difficulty of extensive motion artifacts inherently associated with arterial pulsations in addition to other physiological movements. In this study, we employed a technique involving a fourth order statistical method, kurtosis, operating on the endovascular OCT intensity images to visualize the vasa vasorum of carotid artery in vivo and identify its flow dynamic in a porcine model. The intensity kurtosis technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The present study demonstrates for the first time that OFDI of the human coronary artery accurately corresponds to histology, although VV visualization by OCT in the porcine carotid artery has been previously reported. 10 Unique properties of the OFDI system, including its excellent sensitivity and tissue penetration, 7-9 allow clear visualization of the coronary adventitia. Thus, the OFDI system could be a new modality for VV visualization as compared with the current imaging techniques (eg, IVUS).…”
Section: Images In Cardiovascular Medicine Ofdi Of Adventitial Vasa Vmentioning
confidence: 99%
“…The present study demonstrates for the first time that OFDI of the human coronary artery accurately corresponds to histology, although VV visualization by OCT in the porcine carotid artery has been previously reported. 10 Unique properties of the OFDI system, including its excellent sensitivity and tissue penetration, 7-9 allow clear visualization of the coronary adventitia. Thus, the OFDI system could be a new modality for VV visualization as compared with the current imaging techniques (eg, IVUS).…”
Section: Images In Cardiovascular Medicine Ofdi Of Adventitial Vasa Vmentioning
confidence: 99%
“…Optical coherence tomography (OCT) imaging using optical fiber-based rotary catheter probes provides 2D and 3D visualization of microstructures in tissue and has shown initial success in the cardiovascular [1,2], gastroesophageal [3], and pulmonary systems [4]. These clinical studies suggest that rotary catheters provide useful in-vivo diagnostic information based on the structural morphology in the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by our group, it was also demonstrated that EV-OCT can potentially detect vasa vasorum in vivo. 14 Figure 5 shows a representative image of vasospasm of porcine carotid artery. A 3D reconstruction of the spasm segment is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%